Climate Change and Renewable Energy Consumption Obligations: Response of the Indian Judiciary (GLS Law Journal, 2023)
Climate change accounts for many of the natural disasters in India. Despite India being one of the top five greenhouse gas emitters in the world, policy and legal framework have not so far considered the issue of climate change in perspective. The constitution of India guarantees fundamental rights to its people through Article 21 and the article covers innumerable rights under its grab including right to health, pollution free air and water, sanitation rights, right to food, clean environment etc. India has ratified United Nations Convention on Climate Change (UNFCCC) and the Kyoto Protocol and has now obligations under the Paris Agreement to cut greenhouse gas emissions intensity of its gross domestic product 33% to 35% by 2030. India’s’ target is laudable and ambitious in this regard. The judiciary in India has assumed its primary responsibility towards the individuals to safeguard their interest relating to environmental protection by combating climate change. There are remarkable judgments passed by the higher courts and the Green Tribunal relating to climate change. In Abhimanyu Rathore v State of H. P considering the Kedarnath and Srinagar tragedies the court has pointed out the ecological destruction due to climate change and declared that every citizen has the right to potable drinking water and breath pollution free air. There were also circumstance when the court has ruled in favour of development at the cost of environmental damage that is in the Sardar Sarovar dam project where a dam project with the reservoir level height up to 455 height was permitted by the Supreme Court, The Indian judiciary has wide powers to protect and safeguard the environment and contributed considerably towards the development of environmental jurisprudence in India. This paper is an attempt to analyse the judicial response towards renewable energy obligations and the paper will delve into the various aspects of the same and find out the recent trends.
Keywords: Climate Change; Renewable Energy Consumption; UNFCCC; Green Tribunal